Preparation method of superfine high-moisture-absorption ES hollow fiber

Through the preparation method of ultrafine high-hygroscopic ES hollow fibers, modified fibers are blended with materials such as sulfonated dioctyl succinate sodium salt, and through spinning and secondary drafting treatment, the gap in technology and performance of existing ES fibers is solved, high moisture absorption and moisturizing properties are achieved, and the competitiveness of the product is enhanced.

CN119593105APending Publication Date: 2025-03-11MINRUI IND HOLDINGS (JIANGSU) CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411514817.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

There are gaps in existing ES fibers in terms of technical level, product performance and brand image, resulting in weak international market competitiveness and unable to meet the high requirements for material performance of high-end disposable sanitary products.

Method used

The preparation method of ultrafine high hygroscopic ES hollow fiber is adopted to form fibers with high hygroscopic and moisturizing properties by blending modified leather and core materials of dioctyl succinate sodium salt, fatty alcohol polyoxyethylene ether sodium sulfate, and spinning and secondary drafting treatment.

Benefits of technology

It achieves the high moisture absorption and moisturizing properties of fibers, meets the high requirements for material performance of high-end disposable sanitary products, and enhances the competitiveness of the products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of superfine high-moisture-absorption ES hollow fibers, and relates to the technical field of textiles. According to the invention, polyethylene terephthalate is used as a core layer, steric hindrance of a molecular chain of polyethylene terephthalate is increased through 5-methyl isophthalic acid, diffusion and adsorption of water molecules are facilitated, hygroscopicity is realized, then sulfonated sodium dioctyl succinate is compounded with anionic and cationic surfactants to form a hydrophilic finishing agent, moisture retention of the fiber is realized, and then the fiber is subjected to hydrophilic finishing to form a hydrophilic finishing agent. An inorganic filler is added and is coated through the physical adsorption and chemical reaction effects of stearic acid ester, the number of gaps is increased and channels of water molecules are increased by virtue of the incompatibility of the filler and resin, then during spinning, the hydrophilic finishing agent has an overall anionic property, so that a matrix is assisted to reduce friction, and in a high-speed stretching process, the hydrophilic finishing agent has a hydrophilic property. The chemical fibers are prevented from generating tows which are dispersed and are not easy to wind, and the fibers form a certain physical-mechanical property and a stable structure through secondary stretching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textiles, in particular to a method for preparing ultrafine high-hygroscopic ES hollow fibers. Background Art

[0002] ES fiber is a polyolefin fiber developed by Japan's JNC Corporation (formerly known as Chisso Corporation), and has won the Japan Fiber Society Technical Achievement Award (the highest award in the Japanese textile industry). As a new type of thermal bonding composite fiber, ES fiber has received high praise in the world. The hot air non-woven fabric made of ES fiber as a raw material has the characteristics of softness, low-temperature processing, non-toxicity, non-irritation and lightweight. It is an ideal material for manufacturing disposable sanitary products such as sanitary napkins, infant diapers, and adult diapers. In recent years, with the increase in the market size of disposable sanitary products and the high-end development of terminal maternal and child products and female sanitary products, hot air non-woven fabrics have gradually replaced spunbond non-woven fabrics to become the ideal material for the new generation of disposable sanitary products, which will also have a significant driving force on the market demand for ES fiber. Compared with leading foreign companies, my country's ES fiber industry started late, mainly concentrated in the middle and low-end markets, and its overall independent research and development and innovation capabilities are relatively weak. There is still a certain gap in technical level, product performance, brand image, etc., and its international market competitiveness is relatively weak.

[0003] With the increase of per capita disposable income, the change of parenting concepts, and the improvement of quality of life, people's consumption needs are constantly changing, and the demand for high-quality, high-end and differentiated products is also increasing. People's demands for multi-functional and high-quality products such as sanitary napkins and diapers are gradually increasing, such as "dryness", "breathability", "softness and non-irritation", etc., which also puts higher requirements on the performance and quality of raw materials of products, driving the expansion of the demand for ES fiber. Non-woven fabrics made of ES fiber have good comfort and are ideal materials for manufacturing high-end sanitary napkins and diapers. They are in line with the development trend of high-end consumption and have good development prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing ultrafine high-hygroscopic ES hollow fibers to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing ultrafine high moisture absorption ES hollow fibers, comprising the following preparation steps:

[0006] (1) Mixing sodium salt of dioctyl sulfonate succinate, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water, adjusting the pH of the solution to 7-8 with a 10 wt % potassium hydroxide aqueous solution, heating to 80-95° C., reacting for 3-5 hours, and obtaining a hydrophilic finishing agent;

[0007] (2) 5-methylisophthalic acid and high melting point polyethylene terephthalate are mixed, heated to 250-270° C., reacted for 3-6 hours, a hydrophilic finishing agent, an inorganic filler, a stearate, and white oil are added, and extrusion granulation is repeated twice to obtain a core material;

[0008] (3) mixing low melting point polyethylene, hydrophilic finishing agent, inorganic filler, stearate and white oil, and repeating extrusion granulation twice to obtain a layer material;

[0009] (4) The layer material and the core material are melted separately and then spun through a sheath-core spinneret, wherein the parts of the spinneret holes of the sheath-core spinneret for the layer material and the core material to pass through are the sheath layer through hole and the core layer through hole respectively, and a hollow central tube is provided in the middle of the spinneret hole. During the spinning process, air is passed into the central tube at a pressure of 250 Pa, and finally hollow fibers are obtained. After oiling and water washing, secondary drawing is performed, with the first drawing multiple being 2 times and the second drawing multiple being 1.3 times, to obtain ultrafine high hygroscopic ES hollow fibers.

[0010] Furthermore, in step (1), the mass ratio of dioctyl sodium sulfonate succinate, sodium fatty alcohol polyoxyethylene ether sulfate, benzalkonium bromide, Tween 60, and deionized water is 10-15:5-10:4-7:0.1-1:100.

[0011] Furthermore, in step (2), the mass ratio of 5-methylisophthalic acid, high melting point polyethylene terephthalate, hydrophilic finishing agent, inorganic filler, stearate and white oil is 0.1-0.5:100:1:2-5:0.2-0.5:0.1.

[0012] Furthermore, the process parameters of the extrusion granulation in step (2) are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 265-280° C., and shear rate of 80-150 rpm.

[0013] Furthermore, in step (3), the mass ratio of the low melting point polyethylene, the hydrophilic finishing agent, the inorganic filler, the stearate and the white oil is 100:1:2-5:0.2-0.5:0.1.

[0014] Furthermore, the process parameters of the extrusion granulation in step (3) are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 135-150° C., and shear rate of 80-150 rpm.

[0015] Furthermore, the melting points of the polyethylene terephthalate and the polyethylene in step (2) and step (3) are 250° C. and 120° C., respectively.

[0016] Furthermore, the inorganic filler in step (2) and step (3) is specifically calcium carbonate with a particle size of 25 to 48 μm.

[0017] Furthermore, in step (4), the skin layer components account for 30-50% of the total amount, the core layer components account for 70-50% of the total amount, and the hollowness of the hollow core layer is 20-40% of the cross-sectional area.

[0018] Furthermore, the fineness of the ultrafine high hygroscopicity ES hollow fiber in step (4) is 0.5 dtex.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The fiber of the invention is prepared by respectively blending a modified leather material and a core material with an inorganic filler and a hydrophilic finishing agent, and then undergoing spinning and secondary drawing treatment to achieve the effects of moisture absorption and moisture retention.

[0021] Firstly, polyethylene terephthalate is used as the core layer, and 5-methylisophthalic acid is used to change the symmetry of the internal macromolecules of polyethylene terephthalate, destroy its original regularity, and increase the spatial hindrance of the molecular chain, which is beneficial to the mutual fusion of the molecules at the contact surface of polyethylene terephthalate and low-density polyethylene as the cortex during melt spinning, and form a lightly cross-linked spatial network structure. At the same time, by reducing the crystallinity of the matrix, that is, the tightness of the molecular chain, it is beneficial to the diffusion and adsorption of water molecules and realize hygroscopicity.

[0022] Secondly, sodium sulfonated dioctyl succinate is compounded with anionic and cationic surfactants as a hydrophilic finishing agent for the substrate. The mixed system of anionic and cationic surfactants forms a tighter layer or layers of hydrophilic membranes, that is, multi-layer adsorption or micellar adsorption, so that the hydrophilic groups can be firmly adsorbed on the substrate, thereby improving its surface hydrophilicity. The compounding of sodium sulfonated dioctyl succinate and anions has a better gain effect, so that there is a greater difference between the concentration of the spreading front of the droplets and the bulk concentration of the droplets, forming a larger surface tension gradient, which promotes further spreading of the droplets. In addition, the double-headed hydrophobic end of the sodium sulfonated dioctyl succinate molecular structure has a strong force with the resin matrix, so it is not easy to be washed away by water, thereby achieving moisture retention. When water enters the fiber, under the joint action of the polymer network inside the matrix and a large number of hydrophilic groups, the fiber swells into a gel-like state, has a strong ability to hold water, and is not easy to lose under the action of external forces. , thereby improving the moisturizing performance. Then, inorganic fillers are added to form defects such as pores and voids between the interface and the matrix, and are coated by physical adsorption and chemical reaction of stearic acid esters. At the same time, the long-chain alkyl in the stearic acid ester is connected to the resin matrix to form a bridge, thereby promoting the dispersion of the powder in the resin matrix, and relying on the incompatibility of the filler and the resin to increase the number of voids, increase the channels for water molecules, and further improve the hygroscopic performance. Then, during spinning, the hydrophilic finishing agent is anionic as a whole, has antistatic effect, assists the matrix to reduce friction, and prevents the chemical fiber from being dispersed and difficult to wind during high-speed stretching. After secondary stretching, during the first stretching, the fibers are arranged in an orderly manner along the direction of the external force, so that the macromolecules are oriented and the strength is improved. Then, through the second stretching, the macromolecules are further oriented and crystallized, while reducing the thermal shrinkage of the fibers, so that the fibers form certain physical-mechanical properties and a stable structure. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the ultrafine high moisture absorption ES hollow fibers prepared in the following examples are as follows:

[0025] Hygroscopicity: Take the embodiment and comparative example of the same size and refer to GB / T21655.1 to test their water absorption.

[0026] Hydrophilicity: The embodiment and comparative example of the same size were taken and the contact angle of water was tested by a contact angle meter using a sessile drop method, and the volume of the water drop was 3 μL.

[0027] Moisturizing: Take the same size of the embodiment and the comparative example and refer to GB / T24218.14 to detect their re-seepage amount.

[0028] Example 1; (1) Dioctyl sulfonate sodium salt, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water were mixed, the pH of the solution was adjusted to 7 with 10wt% potassium hydroxide aqueous solution, the temperature was raised to 80°C, and the reaction was carried out for 3h to obtain a hydrophilic finishing agent; the mass ratio of dioctyl sulfonate sodium salt, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water was 10:5:4:0.1:100;

[0029] (2) 5-methylisophthalic acid and polyethylene terephthalate with a melting point of 250°C are mixed, heated to 250°C, reacted for 3 hours, a hydrophilic finishing agent, calcium carbonate with a particle size of 25 μm, stearate, and white oil are added, and extrusion granulation is repeated twice. The process parameters are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 265°C, and shear rate of 80 rpm to obtain a core material; the mass ratio of the 5-methylisophthalic acid, polyethylene terephthalate with a melting point of 250°C, hydrophilic finishing agent, calcium carbonate with a particle size of 25 μm, stearate, and white oil is 0.1:100:1:2:0.2:0.1;

[0030] (3) Mixing polyethylene with a melting point of 120° C., a hydrophilic finishing agent, calcium carbonate with a particle size of 25 μm, a stearate, and white oil, and repeating extrusion granulation twice, wherein the process parameters are as follows: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 135° C., and a shear rate of 80 rpm, to obtain a layer material; the mass ratio of the polyethylene with a melting point of 120° C., the hydrophilic finishing agent, the calcium carbonate with a particle size of 25 μm, the stearate, and the white oil is 100:1:2:0.2:0.1;

[0031] (4) The layer material and the core material are melted separately and then spun through a sheath-core type spinneret, wherein the parts of the spinneret holes of the sheath-core type spinneret for the layer material and the core material to pass through are respectively a sheath through hole and a core through hole, and a hollow central tube is provided in the middle of the spinneret hole. During the spinning process, air is passed into the central tube at an air pressure of 250 Pa, and finally a hollow fiber is obtained, in which the sheath component accounts for 30% of the total amount, the core component accounts for 70% of the total amount, and the hollowness of the hollow core layer is 20% of the cross-sectional area. After oiling and washing, a secondary stretching is performed, in which the first stretching multiple is 2 times and the second stretching multiple is 1.3 times, to obtain an ultrafine high moisture absorption ES hollow fiber with a fineness of 0.5 dtex.

[0032] Example 2; (1) Dioctyl sulfonate sodium salt, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water were mixed, the pH of the solution was adjusted to 7.5 with 10wt% potassium hydroxide aqueous solution, the temperature was raised to 88°C, and the reaction was carried out for 4h to obtain a hydrophilic finishing agent; the mass ratio of dioctyl sulfonate sodium salt, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water was 13:8:5.5:0.6:100;

[0033] (2) 5-methylisophthalic acid and polyethylene terephthalate with a melting point of 250°C are mixed, heated to 260°C, reacted for 4.5 hours, a hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, stearate, and white oil are added, and extrusion granulation is repeated twice. The process parameters are as follows: screw diameter is 20 mm, aspect ratio is 25:1, extrusion temperature is 270°C, and shear rate is 100 rpm to obtain a core material; the mass ratio of the 5-methylisophthalic acid, polyethylene terephthalate with a melting point of 250°C, hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, stearate, and white oil is 0.3:100:1:3.5:0.35:0.1;

[0034] (3) Mixing polyethylene with a melting point of 120° C., a hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, a stearate, and white oil, and repeating extrusion granulation twice, wherein the process parameters are as follows: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 140° C., and a shear rate of 100 rpm, to obtain a layer material; the mass ratio of the polyethylene with a melting point of 120° C., the hydrophilic finishing agent, the calcium carbonate with a particle size of 32 μm, the stearate, and the white oil is 100:1:3.5:0.35:0.1;

[0035] (4) The layer material and the core material are melted separately and then spun through a sheath-core spinneret, wherein the parts of the spinneret holes of the sheath-core spinneret for the layer material and the core material to pass through are respectively a sheath through hole and a core through hole, and a hollow central tube is provided in the middle of the spinneret hole. During the spinning process, air is passed into the central tube at an air pressure of 250 Pa, and finally a hollow fiber is obtained, in which the sheath component accounts for 40% of the total amount, the core component accounts for 60% of the total amount, and the hollowness of the hollow core layer is 30% of the cross-sectional area. After oiling and washing, a secondary stretching is performed, in which the first stretching multiple is 2 times and the second stretching multiple is 1.3 times, to obtain an ultrafine high moisture absorption ES hollow fiber with a fineness of 0.5 dtex.

[0036] Example 3; (1) Dioctyl sulfonate sodium salt, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water were mixed, the pH of the solution was adjusted to 8 with 10wt% potassium hydroxide aqueous solution, the temperature was raised to 95°C, and the reaction was performed for 5h to obtain a hydrophilic finishing agent; the mass ratio of dioctyl sulfonate sodium salt, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water was 15:10:7:1:100;

[0037] (2) 5-methylisophthalic acid and polyethylene terephthalate with a melting point of 250°C are mixed, heated to 270°C, reacted for 6 hours, a hydrophilic finishing agent, calcium carbonate with a particle size of 48 μm, stearate, and white oil are added, and extrusion granulation is repeated twice. The process parameters are as follows: screw diameter is 20 mm, aspect ratio is 25:1, extrusion temperature is 280°C, and shear rate is 150 rpm to obtain a core material; the mass ratio of the 5-methylisophthalic acid, polyethylene terephthalate with a melting point of 250°C, hydrophilic finishing agent, calcium carbonate with a particle size of 48 μm, stearate, and white oil is 0.5:100:1:5:0.5:0.1;

[0038] (3) Mixing polyethylene with a melting point of 120° C., a hydrophilic finishing agent, calcium carbonate with a particle size of 48 μm, a stearate, and white oil, and repeating extrusion granulation twice, wherein the process parameters are as follows: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 150° C., and a shear rate of 150 rpm, to obtain a layer material; the mass ratio of the polyethylene with a melting point of 120° C., the hydrophilic finishing agent, the calcium carbonate with a particle size of 48 μm, the stearate, and the white oil is 100:1:5:0.5:0.1;

[0039] (4) The layer material and the core material are melted separately and then spun through a sheath-core spinneret, wherein the parts of the spinneret holes of the sheath-core spinneret for the layer material and the core material to pass through are respectively a sheath through hole and a core through hole, and a hollow central tube is provided in the middle of the spinneret hole. During the spinning process, air is passed into the central tube at an air pressure of 250 Pa, and finally a hollow fiber is obtained, in which the sheath component accounts for 50% of the total amount, the core component accounts for 50% of the total amount, and the hollowness of the hollow core layer is 40% of the cross-sectional area. After oiling and water washing, a secondary stretching is performed, in which the first stretching multiple is 2 times and the second stretching multiple is 1.3 times, to obtain an ultrafine high moisture absorption ES hollow fiber with a fineness of 0.5 dtex.

[0040] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different, and step (1) is changed to: mixing sodium fatty alcohol polyoxyethylene ether sulfate, benzalkonium bromide, Tween 60 and deionized water, adjusting the solution pH to 7.5 with 10wt% potassium hydroxide aqueous solution, heating to 88°C, reacting for 4h, and obtaining a hydrophilic finishing agent; the mass ratio of the sodium fatty alcohol polyoxyethylene ether sulfate, benzalkonium bromide, Tween 60 and deionized water is 8:5.5:0.6:100; the remaining steps are the same as in Example 2.

[0041] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different, and step (1) is changed to: sodium salt of dioctyl sulfonate succinate, benzalkonium bromide, Tween 60 and deionized water are mixed, the pH value of the solution is adjusted to 7.5 with 10wt% potassium hydroxide aqueous solution, the temperature is raised to 88°C, and the reaction is carried out for 4h to obtain a hydrophilic finishing agent; the mass ratio of sodium salt of dioctyl sulfonate succinate, benzalkonium bromide, Tween 60 and deionized water is 13:5.5:0.6:100; the remaining steps are the same as those in Example 2.

[0042] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (1) is different, and step (1) is changed to: mix sodium salt of dioctyl sulfonate succinate, sodium sulfate of fatty alcohol polyoxyethylene ether, Tween 60 and deionized water, adjust the solution pH to 7.5 with 10wt% potassium hydroxide aqueous solution, heat to 88°C, react for 4h, and obtain a hydrophilic finishing agent; the mass ratio of sodium salt of dioctyl sulfonate succinate, sodium sulfate of fatty alcohol polyoxyethylene ether, Tween 60 and deionized water is 13:8:0.6:100; the remaining steps are the same as Example 2.

[0043] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: polyethylene terephthalate with a melting point of 250°C, a hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, stearate, and white oil are mixed, and extrusion granulation is repeated twice. The process parameters are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 270°C, and shear rate of 100 rpm to obtain a core material; the mass ratio of polyethylene terephthalate with a melting point of 250°C, hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, stearate, and white oil is 100:1:3.5:0.35:0.1; the remaining steps are the same as Example 2.

[0044] Comparative Example 5; The difference between Comparative Example 5 and Example 2 is that there is no step (1), and step (2) is different from step (3), and step (2) is changed to: 5-methylisophthalic acid and polyethylene terephthalate with a melting point of 250°C are mixed, heated to 260°C, reacted for 4.5h, calcium carbonate with a particle size of 32μm, stearate, and white oil are added, and extrusion granulation is repeated twice. The process parameters are: screw diameter of 20mm, aspect ratio of 25:1, extrusion temperature of 270°C, shear rate of 100rpm, and core material is obtained; the mass ratio of the 5-methylisophthalic acid, polyethylene terephthalate with a melting point of 250°C, calcium carbonate with a particle size of 32μm, stearate, and white oil is 0.3:100:3.5:0.35:0.1;

[0045] Step (3) is changed to: polyethylene with a melting point of 120°C, calcium carbonate with a particle size of 32 μm, stearate and white oil are mixed, and extrusion granulation is repeated twice. The process parameters are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 140°C, and shear rate of 100 rpm to obtain a layer material; the mass ratio of the polyethylene with a melting point of 120°C, calcium carbonate with a particle size of 32 μm, stearate and white oil is 100:3.5:0.35:0.1; the remaining steps are the same as Example 2.

[0046] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that step (2) and step (3) are different. Step (2) is changed to: 5-methylisophthalic acid and polyethylene terephthalate with a melting point of 250°C are mixed, the temperature is raised to 260°C, the reaction is carried out for 4.5 hours, a hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, and white oil are added, and extrusion granulation is repeated twice. The process parameters are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 270°C, and shear rate of 100 rpm to obtain a core material; the mass ratio of the 5-methylisophthalic acid, polyethylene terephthalate with a melting point of 250°C, hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, and white oil is 0.3:100:1:3.5:0.1;

[0047] The step (3) is changed to: polyethylene with a melting point of 120°C, a hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, and white oil are mixed, and extrusion granulation is repeated twice. The process parameters are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 140°C, and shear rate of 100 rpm to obtain a layer material; the mass ratio of the polyethylene with a melting point of 120°C, the hydrophilic finishing agent, calcium carbonate with a particle size of 32 μm, and the white oil is 100:1:3.5:0.1; the remaining steps are the same as those in Example 2.

[0048] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that step (2) and step (3) are different. Step (2) is changed to: 5-methylisophthalic acid and polyethylene terephthalate with a melting point of 250°C are mixed, heated to 260°C, reacted for 4.5h, a hydrophilic finishing agent and white oil are added, and extrusion granulation is repeated twice. The process parameters are: screw diameter of 20mm, aspect ratio of 25:1, extrusion temperature of 270°C, shear rate of 100rpm, and core material is obtained; the mass ratio of 5-methylisophthalic acid, polyethylene terephthalate with a melting point of 250°C, hydrophilic finishing agent, and white oil is 0.3:100:1:0.1;

[0049] The step (3) is changed to: polyethylene with a melting point of 120°C, a hydrophilic finishing agent and white oil are mixed, and extrusion granulation is repeated twice, and the process parameters are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 140°C, shear rate of 100 rpm, to obtain a layer material; the mass ratio of the polyethylene with a melting point of 120°C, the hydrophilic finishing agent and the white oil is 100:1:0.1; the remaining steps are the same as those in Example 2.

[0050] Effect example

[0051] Table 1 below shows the performance analysis results of the ultrafine high moisture absorption ES hollow fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.

[0052] Table 1

[0053] Water absorption (%) Contact angle (°) Re-seepage amount (g) Example 1 475 27.54 0.86 Example 2 480 27.31 0.82 Example 3 470 27.69 0.85 Comparative Example 1 445 29.67 0.94 Comparative Example 2 465 27.93 0.87 Comparative Example 3 460 28.15 0.88 Comparative Example 4 450 29.86 0.99 Comparative Example 5 420 33.23 1.06 Comparative Example 6 450 28.98 0.91 Comparative Example 7 405 31.72 1.13

[0054] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses polyethylene terephthalate as the core layer, and changes the symmetry of the internal macromolecules of polyethylene terephthalate by 5-methylisophthalic acid, thereby increasing the spatial hindrance of the molecular chain, which is beneficial to the mutual fusion of the molecules between the contact surfaces of polyethylene terephthalate and the low-density polyethylene as the cortex during melt spinning, and forms a slightly cross-linked spatial network structure, which is beneficial to the diffusion and adsorption of water molecules and realizes hygroscopicity. Then, sulfonated dioctyl sodium salt is compounded with anionic and cationic surfactants as a hydrophilic finishing agent for the matrix, wherein the anionic and cationic surfactant mixed system forms a tighter layer or layers of hydrophilic film, thereby improving its surface hydrophilicity, and the compounding of sulfonated dioctyl sodium salt with anions has a better gain effect, so that there is a greater difference between the spreading front concentration of the droplets and the bulk concentration of the droplets, forming a larger surface tension gradient, promoting further spreading of the droplets, and the double-headed hydrophobic end in the molecular structure of sulfonated dioctyl sodium salt and the resin Due to the strong interaction between the matrix, it is not easy to be washed away by water, thus achieving moisture retention. When water enters the fiber, under the joint action of the polymer network and a large number of hydrophilic groups inside the matrix, the fiber swells into a gel state, and is not easy to lose under the action of external force, thereby improving the moisture retention performance. Then, inorganic fillers are added to form defects such as pores and voids between the matrix interface, and are coated by physical adsorption and chemical reaction of stearic acid esters. At the same time, the long-chain alkyl in the stearic acid ester is connected to the resin matrix to form a bridge, thereby promoting the dispersion of the powder in the resin matrix, and relying on the incompatibility of the filler and the resin to increase the number of voids, increase the channels for water molecules, and further improve the moisture absorption performance. Then, during spinning, the hydrophilic finishing agent is anionic as a whole, has antistatic effect, assists the matrix to reduce friction, and prevents the chemical fiber from producing bundle dispersion and difficult winding during high-speed stretching. Then, through the second stretching, the macromolecules are further oriented and crystallized, while reducing the thermal shrinkage of the fiber, so that the fiber forms certain physical-mechanical properties and a stable structure.

[0055] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing ultrafine high hygroscopic ES hollow fibers, characterized in that: The method comprises the following preparation steps: (1) Mixing sodium salt of dioctyl sulfonate succinate, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water, adjusting the pH of the solution to 7-8 with a 10 wt % potassium hydroxide aqueous solution, heating to 80-95° C., reacting for 3-5 hours, and obtaining a hydrophilic finishing agent; (2) 5-methylisophthalic acid and high melting point polyethylene terephthalate are mixed, heated to 250-270° C., reacted for 3-6 hours, a hydrophilic finishing agent, an inorganic filler, a stearate, and white oil are added, and extrusion granulation is repeated twice to obtain a core material; (3) mixing low melting point polyethylene, hydrophilic finishing agent, inorganic filler, stearate and white oil, and repeating extrusion granulation twice to obtain a layer material; (4) The layer material and the core material are melted separately and then spun through a sheath-core spinneret, wherein the parts of the spinneret holes of the sheath-core spinneret for the layer material and the core material to pass through are the sheath layer through hole and the core layer through hole respectively, and a hollow central tube is provided in the middle of the spinneret hole. During the spinning process, air is passed into the central tube at a pressure of 250 Pa, and finally hollow fibers are obtained. After oiling and water washing, secondary drawing is performed, with the first drawing multiple being 2 times and the second drawing multiple being 1.3 times, to obtain ultrafine high hygroscopic ES hollow fibers.

2. The method for preparing the ultrafine high hygroscopic ES hollow fiber according to claim 1, characterized in that: The mass ratio of the sodium salt of dioctyl sulfonate succinate, sodium sulfate of fatty alcohol polyoxyethylene ether, benzalkonium bromide, Tween 60 and deionized water in step (1) is 10-15:5-10:4-7:0.1-1:

100.

3. The method for preparing ultrafine high hygroscopic ES hollow fibers according to claim 1, characterized in that: The mass ratio of the 5-methylisophthalic acid, high melting point polyethylene terephthalate, hydrophilic finishing agent, inorganic filler, stearate and white oil in step (2) is 0.1-0.5:100:1:2-5:0.2-0.5:0.

1.

4. The method for preparing ultrafine high hygroscopic ES hollow fibers according to claim 1, characterized in that: The process parameters of the extrusion granulation in step (2) are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the extrusion temperature is 265-280° C., and the shear rate is 80-150 rpm.

5. The method for preparing ultrafine high hygroscopic ES hollow fibers according to claim 1, characterized in that: In step (3), the mass ratio of the low melting point polyethylene, the hydrophilic finishing agent, the inorganic filler, the stearate and the white oil is 100:1:2-5:0.2-0.5:0.

1.

6. The method for preparing ultrafine high hygroscopic ES hollow fibers according to claim 1, characterized in that: The process parameters of the extrusion granulation in step (3) are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the extrusion temperature is 135-150° C., and the shear rate is 80-150 rpm.

7. The method for preparing ultrafine high hygroscopic ES hollow fibers according to claim 1, characterized in that: The melting points of the polyethylene terephthalate and polyethylene in step (2) and step (3) are 250° C. and 120° C. respectively.

8. The method for preparing ultrafine high hygroscopic ES hollow fibers according to claim 1, characterized in that: The inorganic filler in step (2) and step (3) is specifically calcium carbonate with a particle size of 25 to 48 μm.

9. The method for preparing ultrafine high hygroscopic ES hollow fibers according to claim 1, characterized in that: In step (4), the skin layer components account for 30-50% of the total amount, the core layer components account for 70-50% of the total amount, and the hollowness of the hollow core layer is 20-40% of the cross-sectional area.

10. The method for preparing ultrafine high hygroscopic ES hollow fibers according to claim 1, characterized in that: The fineness of the ultrafine high hygroscopicity ES hollow fiber in step (4) is 0.5 dtex.

Citation Information

Cited By

  • ES hollow fiber and manufacturing process thereof

    CN121087644A